Democracy and Authoritarianism in Egypt Today - Patrick Ziegenhain; Khaliunaa Enkhtaivan (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2024)
In this paper, we analyze the political system of Egypt under President Abdel Fattah Al-Sisi between 2016 and 2024. The article aims to reveal whether there are still some democratic elements or if the country has rather a classical authoritarian system. To answer this question, we used relevant democracy criteria as analytical tools. Methodologically, we conducted this study through a literature review and an expert interview with an Egyptian political scientist. Based on the findings on vertical accountability, political rights, civil liberties, and horizontal accountability, Egypt has quite an authoritarian regime with few democratic elements.